2011
DOI: 10.1007/s10658-011-9848-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Aphanomyces cochlioides on selected physiological processes in sugar beet leaves and yield parameters

Abstract: Alterations in some physiological processes in source leaves of sugar beet-such as chlorophyll and carbohydrate concentrations, stomatal conductance, rate of net photosynthesis and transpiration, and activity of the photosynthetic apparatus during root interaction with Aphanomyces cochlioides, were investigated. The influence of time of infection on plant health, yield quality and quantity was also examined. Plants were infected at different times of their growth period: on the sowing day and 4 or 8 weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A decrease in photosynthesis has been reported in compatible interactions with biotrophic fungi, i.e., Albugo candida, Puccinia coronata and Blumeria graminis (Chou et al 2000;Scholes and Rolfe 1996;Swarbrick et al 2006) as well as necrotrophic pathogens such as Botrytis cinerea (Berger et al 2004(Berger et al , 2007. The photosynthetic organs of young leaves of sugar beet are particularly sensitive to the infection by Aphanomyces cochlioides (oomycetes) (Chołuj and Moliszewska 2012).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…A decrease in photosynthesis has been reported in compatible interactions with biotrophic fungi, i.e., Albugo candida, Puccinia coronata and Blumeria graminis (Chou et al 2000;Scholes and Rolfe 1996;Swarbrick et al 2006) as well as necrotrophic pathogens such as Botrytis cinerea (Berger et al 2004(Berger et al , 2007. The photosynthetic organs of young leaves of sugar beet are particularly sensitive to the infection by Aphanomyces cochlioides (oomycetes) (Chołuj and Moliszewska 2012).…”
Section: Sugar Sensing and Signalingmentioning
confidence: 99%
“…Simultaneously the levels of sugar and carbohydrate were significantly lowest in -sensitive cultivars of cut roses at both developmental stages. Although many reports have suggested that sugars act a prime sensing mechanism to pathogen attack [ 51 , 52 , 53 , 54 ]. However, our results indicate that sugars and carbohydrates act a prime inducing precursor to aphid tolerance only in resistant cultivars compared to sensitive cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Symptoms of Aphanomyces root rot (1, 2) and of girth scab given by (A) Benada et al (1984), (B) by Hinfner and Homonnay (1966), and (C) symptoms of seedling damping-off given by Benada et al (1984) showed different susceptibility to the damage caused by a. cochlioides (Moliszewska 2009). Chołuj and Moliszewska (2012) proved that the severity of the disease increases in conditions favourable for the pathogen (hot and wet conditions, the experiment was realised in a greenhouse). The disease develops if the pathogen inoculum is at an appropriate level in a period of about one month after sowing, even if the seed protection was applied.…”
Section: Investigation Of the Sugar Beet Root Rotmentioning
confidence: 95%
“…Like in other soil-borne diseases, its control is difficult. Crop protection should usually be based on seed treatment with fungicides, use of cultivars with higher levels of resistance, management of soil moisture, long rotations with non-host crops and weed control (Szymczak-Nowak 1987;Asher 1992;Beale et al 2002;Pearsson & Olsson 2005;Chołuj & Moliszewska 2012;Nechwatal et al 2012). Moliszewska (2009) experiments in 2003, which started from the investigation of seedling diseases.…”
Section: Aphanomyces Cochlioides On Sugar Beet In Central Europementioning
confidence: 99%
See 1 more Smart Citation